Harmonic current effect on the sizing of neutral conductor of low voltage distribution network - Azharudin, Mukhtaruddin
Power system harmonic phenomenon was an old problem, but with renewed and unprecedented threat. This matter deserved to get a refreshing look as proliferation of non-linear loads, one of the harmonic sources, has been increasing exponentially especially at low voltage network. Despite this fact, research into the problem seemed to be declining. Firstly the effect of harmonic current in low voltage, balanced three-phase system has been researched. Cable sizes involved in this study were 2.5 mm2 to 16 mm2. This level of system has been thought to be important since interaction between users, trained or not, and systems was commonly taken place. Secondly how harmonic eventually neutral conductor sizing has been studied. It has been confirmed that with the increased of harmonic content, neutral current value would be increased. In addition, neutral conductor initial ampacity has been found to be de-rated under the presence of harmonic. Harmonic derating factor, heating effect method, proposed techniques by Arthur and Shanahan, followed by Chindris as well as guidelines from IEC and NEC standards have been identified to be applied to determine the neutral conductor sizing under harmonic presence. Analysis of results from each method as well as their performance has been done. Simulation and analysis using Fast Fourier Transform has been carried out using MATLAB environment. Comparison between each method including comparison to the basic conductor sizing formulation has also been carried out. It has been concluded that each method, including those proposed by standards, had its own shortcomings. By further analysing results from two of the methods, two new mathematical relationships that correlate harmonic content and neutral conductor sizing have been developed. One of the two formulations has been identified as the best based on several criteria. This formula contributes towards correct, faster and shorter step of determining neutral conductor sizing under harmonic presence.